Automatização do Modelo Rojo de Análise Fundamentalista - Delalibera, Wesley (2023)
This dissertation aimed to develop a technical product to automate the Rojo (2014) fundamental analysis model, in order to assist investors in initiating their own long-term investment analysis in the Brazilian stock market. Through research conducted with investors who achieved returns above the market average, Rojo (2014) collected the five main variables used as criteria by these investors to initiate an analysis of investment opportunities in the stock market. The construction of the tool, the object of this work, is based primarily on the Rojo (2014) model, and complementarily on other authors and works developed on the topic. This research can be classified as an applied research, characterized as exploratory. Regarding the approach, it is a qualitative research, as it employs a specific model developed by the author. The technical product was developed using the Microsoft Excel program and uses a historical database to verify which stocks listed on the Brazilian exchange meet the established variables and conditions, assigning weights and displaying as output a list of stocks ordered by the sum of these weights. The database used by the tool was extracted from multiple free sources, such as the Brazilian Securities Commission, Google Finance, Yahoo Finance and the website www.fundamentus.com.br. The tool can be downloaded through the website: https://bit.ly/AF-PRODUTO-TECNICO.